Coexistence of Bilirubin ≥10 mg/dL and Prothrombin Time-International Normalized Ratio ≥1.6 on Day 7: A Strong Predictor of Early Graft Loss After Living Donor Liver Transplantation. Issue 3 (March 2018) - Okamura, Yusuke; Yagi, Shintaro; Sato, Toshiya; Hata, Koichiro; Ogawa, Eri; Yoshizawa, Atsushi; Kamo, Naoko; Yamashiki, Noriyo; Okajima, Hideaki; Kaido, Toshimi; Uemoto, Shinji
Abstract : Background: Early allograft dysfunction (EAD) defined by serum total bilirubin (TB) of 10 mg/dL or greater or prothrombin time-international normalized ratio (PT-INR) of 1.6 or greater on postoperative day 7 (POD 7) or aminotransferase greater than 2000 IU/L within the first week, is associated with early graft loss after deceased-donor liver transplantation. We aimed to determine the prognostic impact of the EAD definition in living-donor liver transplantation (LDLT). Methods: We analyzed the validity of the EAD definition and its impact on early graft survival in 260 adult recipients who underwent primary LDLT. Results: Eighty-four (32.3%) patients met the EAD criteria; 59 (22.7%) and 46 (17.7%) patients had TB of 10 mg/dL or greater and PT-INR of 1.6 or greater on POD 7, respectively, and 22 (8.5%) patients satisfied both criteria. Graft survival differed significantly when stratified according to TB of 10 mg/dL or greater and PT-INR of 1.6 or greater ( P < 0.0001). PT-INR of 1.6 or greater resulted in higher graft mortality (risk ratio [RR], 3.87; P < 0.0001 at 90 days; RR, 2.97; P < 0.0001 at 180 days), as did TB of 10 mg/dL or greater (RR, 1.89; P = 0.027 at 90 days; RR, 1.91; P = 0.006 at 180 days). Coexistence of TB of 10 mg/dL or greater and PT-INR of 1.6 or greater was strongly associated with early graft loss (59.1%, RR, 6.97 at 90 days; 68.2%; RR, 5.75 at 180 days). In Cox regression analysis, PT-INR of 1.6 or greater and TB of 10 mg/dL or greater on POD 7 were significant risk factors for early graft loss (hazard ratio, 4.10; 95% confidence interval, 2.35-7.18; P < 0.0001, and hazard ratio, 2.43; 95% confidence interval, 1.39-4.24; P = 0.0018, respectively). Conclusions: TB of 10 mg/dL or greater and/or PT-INR of 1.6 or greater on POD 7 predicted early graft loss after LDLT, and their coexistence worsened patient outcomes. Abstract : In this retrospective study, the authors show that 2 of 3 "early allograft dysfunction" criteria, namely total bilirubin ≥10 mg/dL and/or PT-INR ≥1.6 on postoperative day 7 are useful predictors of early graft loss after LDLT.